Agency, Cultural and Theological Representation of Ecological Narrative in Indonesian Popular Islamic Websites - Saad, Mukhlisin; Umar Faruq (JURNAL PENELITIAN, 2024)
This article addresses a notable gap in the existing scholarly discourse on Islamic ethics by investigating the dissemination of ecological perspectives within the digital realm, with a specific focus on two prominent exceptions in the Indonesian online Islamic sphere: islami.co and alif.id. While the broader academic attention to Islamic ethics and ecology has been extensive, there has been a lack of exploration into the strategies employed by digital platforms to propagate ecological perspectives. Concurrently, prevailing Islamic websites tend to prioritize contemporary Islamic laws and modernity, emphasizing concerns predominantly related to humanity rather than ecological matters. The research illuminates how islami.co and alif.id distinguish themselves by significantly emphasizing ecological issues, providing substantial content dedicated to addressing contemporary ecological challenges. By employing framing and representation theory as its analytical framework, the article contends that these Islamic portals have demonstrated a proactive emphasis on ecological issues since the period of 2019-2020, coinciding with the onset of the COVID-19 pandemic. The research elucidates how islami.co and alif.id integrate Islamic theological foundations to the narrative of ecological concerns, while at the same time, they attempt to represent an emphasized nuance of cultural and ecological agencies in maintaining the issue of contemporary ecology